2014
DOI: 10.1111/zph.12167
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Veterinary Antimicrobial Use in the Netherlands. The Dutch Success Model

Abstract: Impacts• Veterinary overuse of antimicrobials contributes to the selection and spread of antimicrobial resistance which poses a public health risk.• A series of events and discoveries of significant reservoirs of antimicrobial resistant pathogens in the Netherlands resulted in a successful collaboration between government and stakeholders to reduce antimicrobial use in farm animals.• Total use of antimicrobials in farm animals in the Netherlands decreased with 56% in the period 2007-2012.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
191
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(201 citation statements)
references
References 43 publications
(50 reference statements)
4
191
0
6
Order By: Relevance
“…As a consequence, there is a tendency to argue against flock treatment of farm animals. A large proportion of the reduction in the amount of antimicrobials used to treat farm animals in the Netherlands has been reported to be due to the restricted use of flock treatment (33), and legal restrictions specifying certain preconditions on the use of flock medication have been gradually introduced in Denmark. Although the phasing out of oral flock treatment leads to less antibiotic usage, it has never been thoroughly investigated whether this also leads to less resistance under field conditions, where untreated animals are housed in close proximity to treated animals, and we tried to answer this question in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, there is a tendency to argue against flock treatment of farm animals. A large proportion of the reduction in the amount of antimicrobials used to treat farm animals in the Netherlands has been reported to be due to the restricted use of flock treatment (33), and legal restrictions specifying certain preconditions on the use of flock medication have been gradually introduced in Denmark. Although the phasing out of oral flock treatment leads to less antibiotic usage, it has never been thoroughly investigated whether this also leads to less resistance under field conditions, where untreated animals are housed in close proximity to treated animals, and we tried to answer this question in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Complementary mandatory measures were implemented, including the use of susceptibility testing before any prescription of CIA for curative purposes. To avoid competition among veterinary practices and therefore potential pressure in antimicrobial prescription and to promote farmer-veterinary relationships and farmer’s education, Dutch farmers were asked by the government to choose only one veterinary practice to provide oversight and prescription in their herds (Speksnijder et al, 2015b). In France, a “Plan Ecoantibio” program was initiated in 2012 and lasts until 2017.…”
Section: Factors Influencing Antimicrobial Use: the Crucial Issue Of mentioning
confidence: 99%
“…First, given the public concern, European governments concluded that animal care in situations of infectious diseases can no longer be left to the discretion of the individual farmer only (Cf. Speksnijder et al 2015;Levy 2014). As a result, policies and regulations have been drafted.…”
Section: From Problems To Opportunitiesmentioning
confidence: 99%